Percutaneous extraction of a leadless Micra pacemaker after dislocation: a case report. Issue 3 (13th July 2019) - Fichtner, Stephanie; Estner, Heidi L; Näbauer, Michael; Hausleiter, Jörg
Abstract: Background : Leadless pacemaker implantation rates are increasing worldwide. Until now leadless pacemaker dislocation and extraction has been rarely reported. Case summary : An 83-year-old patient with cardiac amyloidosis, chronic atrial fibrillation, and complete heart block was implanted with a leadless pacemaker (Micra, Medtronic). On the day after implantation, the device showed an exit block and on cardiac echocardiography and cardiac computer tomography, a device dislocation could be detected. During the day, the device moved at least three times between the tricuspid valve and the right ventricular apex. Each time causing non-sustained ventricular tachycardia. At the next day device extraction was scheduled. After 189 minutes of procedure time, it was possible to retrieve the device with the help of two steerable introducers (Agilis) and two snare catheters. Discussion : Implantable transcatheter leadless pacemakers can be implanted safely most of the time. However, in rare cases device dislocations may occur. Device extraction is possible, but is described as challenging in most published cases